1997
DOI: 10.1034/j.1399-3054.1997.1000103.x
|View full text |Cite
|
Sign up to set email alerts
|

The peribacteroid membrane

Abstract: 1997. The peribacteroid membrane. -Physiol. Plant. 100: 30^4.The objective of this review is to summarise current knowledge about the structure and function of the peribacteroid membrane from the root nodules of leguminous plants. The information is presented in terms of development of this symbiotic membrane from its origin, through proliferation and in the mature state. There are clear indications that the peribacteroid membrane has a distinct structure and function at each developmental stage. The mature pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
(75 reference statements)
0
34
0
Order By: Relevance
“…As discussed previously , such proteins can be expected in the symbiosomes and at the PBM because other studies have shown the involvement of endomembranes in the formation of symbiosomes (for review, see Whitehead and Day, 1997). Interestingly, many ER and Golgi proteins were also detected in the proteome study of phagosomes, the key organelles of macrophages (Garin et al, 2001).…”
Section: Endomembrane and Pm Proteinsmentioning
confidence: 87%
See 2 more Smart Citations
“…As discussed previously , such proteins can be expected in the symbiosomes and at the PBM because other studies have shown the involvement of endomembranes in the formation of symbiosomes (for review, see Whitehead and Day, 1997). Interestingly, many ER and Golgi proteins were also detected in the proteome study of phagosomes, the key organelles of macrophages (Garin et al, 2001).…”
Section: Endomembrane and Pm Proteinsmentioning
confidence: 87%
“…The PBM plays a central role in the exchange of compounds between the organisms (see Udvardi and Day, 1997). To fulfill this role, the PBM is supplied with the specific components, like transporters and enzymes, necessary for the symbiotic exchange processes (see Verma and Hong, 1996;Whitehead and Day, 1997). Several of these activities have been characterized by biochemical and biophysical studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we conclude that functional symbiosomes do not seem to have a true vacuolar nature but remain as an apoplastic-like compartment. The switch to the MtVAMP721d/e controlled exocytotic pathway allows the targeting of vesicles with a different cargo, and this facilitates the formation of a symbiotic interface with specific protein composition (34).…”
Section: Mtvamp721d and Mtvamp721e Localize At The Site Of Bacterialmentioning
confidence: 99%
“…The symbiosome membrane (SM) 1 originates from invaginated plasma membrane as the bacteria enter infected cells, but quickly becomes specialized as the symbiosis matures (3). Within symbiosomes of nodules, the rhizobia continue to multiply before differentiating into bacteroids in which symbiosis-related genes are induced (4).…”
mentioning
confidence: 99%